HUBUNGAN TINGKAT STRES DENGAN KUALITAS TIDUR MAHASISWA KESEHATAN TINGKAT AKHIR DI UNIVERSITAS SARI MULIA - Ruriyanty.R, Nurul Rizka; ., Subhannur Rahman; Mohtar, M. Sobirin; ., Mohammad Basit (STIKES Suaka Insan, 2023)
Stress impacts the physical well-being of final-year students health, particularly in terms of sleep patterns that affect sleep quality. This study aims to determine the relationship between stress levels and sleep quality among final-year students health at Sari Mulia University, Banjarmasin. Sampel in this study was 162 final year students health dengan simple random sampling technique. The study employed a descriptive correlational design with a cross-sectional approach. Data analysis was using Spearman Rho. The study findings revealed that 67 respondents (41.4%) experienced moderate stress, 50 respondents (30.9%) experienced mild stress, and 45 respondents (27.8%) experienced severe stress. Poor sleep quality was 104 respondents (64.2%), while good sleep quality was reported by 58 respondents (35.8%). The Spearman's Rho analysis showed a significant relationship between stress levels and sleep quality, with a strong correlation (p-value 0.000 <0.05, correlation coefficient 0.646). Keywords: Students, Sleep Quality, Stress Level